Model Pembelajaran Sinektik Berbasis STTDG-RWAPS Dengan Penguatan Pendidikan Karakter Dalam Pembelajaran Bahasa Indonesia di SMP - Sumarti Gufron Diyah (J-Simbol: Jurnal Magister Pendidikan Bahasa dan Sastra Indonesia, 2019)
This study aims to describe the design of the STTDG-RWAPS Indonesian Language learning model by strengthening characteristics education (affective value and critical attitude). This study used a qualitative approach with phenomenological methods. The research design used was descriptive -qualitative. The data were taken from all the teachers' directive speech acts in learning Indonesian in class VII, VIII, IX. The source of this research data is Indonesian language teachers who come from different ethnic groups, namely Lampung, Palembang, Sunda, and Java. Based on the qualitative data analysis of the students' answers to the open questionnaire, it was found that all students (100%) were happy to take part in the study using the STTDG-RWAPS-based synectic model. This can be seen from the score of the writing ability average of students who reached 7.5 or good. In fact, there are students’ writings that can be said to be very good (score 95) because the ideas written are very interesting, the use of rules-compliant language.Penelitian ini bertujuan untuk mendeskripsikan desain model pembelajaran Bahasa Indonesia berbasis STTDG-RWAPS dengan penguatan pendidikan karakter (nilai afektif dan sikap kritis). Penelitian ini menggunakan pendekatan kualitatif dengan metode fenomenologis dengan demikian, desain penelitian yang digunakan adalah deskriptif-kualitatif . Data penelitian meliputi semua tindak tutur direktif guru dalam pembelajaran Bahasa Indonesia di kelas VII, VIII, IX. Sumber data penelitian ini adalah guru Bahasa Indonesia yang berasal dari suku bangsa yang berbeda, yakni Lampung, Palembang, Sunda, dan Jawa. Berdasarkan analisis data kualitatif jawaban siswa pada angket terbuka diketahui bahwa seluruh siswa (100%) merasa senang mengikuti pembelajaran tersebut dengan model sinektik berbasis STTDG-RWAPS.Kata Kunci: Pembelajaran, STTDG-RWAPS, fenomenologis , model sinektik